Realizing a Conscious and Receptive Heart Community Occupational Therapists’ Experiences of the Therapeutic Relationship: A Phenomenological Study - Van Schyndel, Rebecca (Université d'Ottawa / University of Ottawa, 2022)
Abstract: Aim: There is limited understanding of therapeutic relationships in community occupational therapy from a psychodynamic perspective. I explored community occupational therapists’ lived experiences of therapeutic relationships with special attention to countertransference. Methods: Interpretive and descriptive phenomenology was used. Eight occupational therapists with experience providing occupational therapy to people in their homes completed two qualitative interviews. Epoche and reduction analysis methods were applied during the thematic analysis and phenomenological writing phases of the study. Findings: Themes related to the therapeutic relationship illuminated tensions therapists experienced between 1) the need to obtain “buy-in” from clients and insecurity regarding their expertise and the potential effectiveness of occupational therapy; 2) self-disclosure and self-protection, and 3) “planting the seed” and feeling responsible for immediate therapeutic outcomes. Therapists voiced difficulty understanding the concept of countertransference but were able to provide powerful examples. They experienced objective, subjective, positive, and negative countertransference. Themes included: 1) fear: experiencing physical vulnerability; 2) sadness: experiencing emotional vulnerability; and 3) frustration: experiencing social vulnerability, all of which impacted therapists’ conscious and unconscious behaviours. Discussion: When reflected upon, countertransference appeared to be a powerful source of information during therapeutic clinical reasoning. It informed the therapists’ use of therapeutic skills including boundary setting, self-disclosure, compassion, empathy, and containment in a diverse array of therapeutic relationships. Significance: Occupational therapy may benefit from a more transparent discussion and acceptance of the emotional dimensions of practice. Integrating a greater awareness and understanding of the intersubjective dynamics of the therapeutic relationship in practice may be beneficial for community occupational therapists.
Keywords: community occupational therapy; therapeutic relationship; countertransference; intersubjectivity; intersubjective dynamics